(untitled) (Contemporary Mathematics, 2025)
In this paper, we are concerned with the Cauchy problem for a reaction-diffusion equation with time-dependent absorption, posed on the Heisenberg group , driven by the sub-Laplacian and supplemented with non-negative integrable initial data. The equation includes a nonlinear absorption term of the form, where, and is a locally integrable function. The main focus is on how the interplay between nonlinear absorption and diffusion determines the long-time behavior of solutions. We show that the nonlinear term determines the large-time asymptotic behavior when, while the classical/anomalous diffusion effects win if , where is the homogeneous dimension of Hn. The novelty of this work lies in extending the asymptotic analysis of nonlinear parabolic equations with time-dependent absorption from the classical Euclidean setting to the sub-Riemannian geometry of the Heisenberg group. To our knowledge, this is the first classification of large-time behavior for such equations in this setting. Our analysis relies on different mathematical techniques tailored to the nature of the results. The proof of the main decay result uses estimates for the solutions along with a comparison principle, while for the sub-critical case, we apply the method of nonlinear capacity estimates, also known as the rescaled test function method, which is particularly effective in capturing subtle asymptotic behavior.